Prognostic Value of Total Bilirubin in Patients With ST-Elevated Myocardial Infarction Undergoing Primary Coronary Intervention - Gul, Mehmet; Uyarel, Huseyin; Ergelen, Mehmet; Akgul, Ozgul; Karaca, Gurkan; Turen, Selahattin; Ugur, Murat; Erturk, Mehmet; Kul, Seref; Surgit, Ozgur; Bozbay, Mehmet; Uslu, Nevzat (My University, 2013)
Previous studies have shown that the serum total bilirubin (TB) concentration was inversely related with stable coronary artery disease, diabetes mellitus, hypertension, and metabolic syndromes. The relation between TB levels and in-hospital and long-term outcomes in patients with ST-segment elevation myocardial infarction (STEM!) who undergo primary percutaneous coronary intervention (PCI) is not known. Data from 1,624 consecutive patients with STEMI who underwent primary PCI were evaluated. TB was measured after primary PCI, and the study population was divided into tertiles. The high TB group (n = 450) was defined as a value in the upper third tertile (>0.9 mg/dl) and the low TB group (n = 1,174) as any value in the lower 2 tertiles (0.90 mg/dl was identified as an effective cutpoint in patients with STEMI for in-hospital cardiovascular mortality (area under the curve 0.66, 95% confidence interval 0.55 to 0.76, p = 0.001). The mean follow-up period was 26.2 months. No differences were seen in the long-term mortality rates between the 2 groups. In conclusion, high TB is independently associated with in-hospital adverse outcomes in patients with STEMI who undergo primary PCI. However, no association was found with long-term mortality. (C) 2013 Elsevier Inc. All rights reserved. (Am J Cardiol 2013;111:166-171)
Keywords: Myocardial Infarction